2020
DOI: 10.1177/1948550620927269
|View full text |Cite
|
Sign up to set email alerts
|

How USA-Centric Is Psychology? An Archival Study of Implicit Assumptions of Generalizability of Findings to Human Nature Based on Origins of Study Samples

Abstract: Conclusions about human behavior are primarily based upon observations from western, educated, industrialized, rich, and democratic (WEIRD) samples, especially from the United States. One consequence may be the promotion of assumptions that research findings from these populations are more generalizable to humankind than findings from non-WEIRD populations. We tested this with an archival study comparing the extent to which titles of over 5,000 published psychology articles specify samples’ racial/ethnic/natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
139
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(168 citation statements)
references
References 20 publications
5
139
0
3
Order By: Relevance
“…Second, our sample was composed of participants from a single cultural background (i.e., Japanese culture). The generalizability of the results should be considered carefully, in the same way as knowledge from the US undergraduates or the Western, Educated, Industrialized, Rich, and Democratic (WEIRD) sample should not be naively applied to samples from other cultures (Cheon et al 2020;Henrich et al 2010). In fact, preceding studies have indicated that Japanese participants were more likely to rely on upper facial features, such as the eyes, while participants from other cultures (e.g., the U.S.) relied on lower facial features (Ozono et al 2010;Yuki et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Second, our sample was composed of participants from a single cultural background (i.e., Japanese culture). The generalizability of the results should be considered carefully, in the same way as knowledge from the US undergraduates or the Western, Educated, Industrialized, Rich, and Democratic (WEIRD) sample should not be naively applied to samples from other cultures (Cheon et al 2020;Henrich et al 2010). In fact, preceding studies have indicated that Japanese participants were more likely to rely on upper facial features, such as the eyes, while participants from other cultures (e.g., the U.S.) relied on lower facial features (Ozono et al 2010;Yuki et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The participants were recruited from MTurk (USA) and Prolific (UK). Both samples were more representative of their countries than university student samples, but the results may have limited generalizability to populations that are not Western, Educated, Industrialized, Rich, and Democratic (Cheon et al, 2020;Henrich et al, 2010). In particular, overestimation of others' self-interest may be inflated by social norms of self-interest in individualistic societies.…”
Section: Constraints On Generalitymentioning
confidence: 94%
“…The authors calculated the odds of a random U.S. undergraduate participating in research published in the Journal of Personality and Social Psychology as 4,000 times more likely than a randomly selected person from the vast majority of humanity living outside North America, Europe, Australia, and Israel. Another analysis found that research involving U.S. samples was less likely to specify sample characteristics in the title compared to research from other regions-unless the research involved work with racial, ethnic, and/or cultural minorities, in which case titles referred to sample characteristics (e.g., "Developmental trajectories of African American youths" but not "Developmental trajectories of White American youths;"Cheon, Melani, & Hong, 2020). Thus, psychologists (particularly White psychologists; Roberts, Bareket-Shavit, Dollins, Goldie, & Mortenson, 2020) tend to treat the behaviors and experiences of White American participants-but not all other people-as generalizable to humankind.…”
mentioning
confidence: 99%